2017
DOI: 10.1016/j.kjms.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gripping volume in the mechanical strengths of orthodontic mini‐implant

Abstract: The objective of study was to investigate the correlation between the mechanical strengths [insertion torque (IT); resonance frequency (RF); and horizontal pullout strength (HPS)] and gripping volume (GV) of mini-implants. Thirty mini-implants of three types (Type A: 2 mm × 10 mm, cylindrical, titanium alloy; Type B: 2 mm × 10 mm, tapered, stainless steel; and Type C: 2 mm × 11 mm, cylindrical, titanium alloy) were inserted 7 mm into artificial bones. One-way analysis of variance and Spearman's test were appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…The principal determinants for mini-implant stability are mechanical retention, mini-implant design, quality and quantity of bone, and placement technique. 10 The firmness of cortical bone is one of the primary factors controlling the stability of mini-implants. 11 Several researchers have attempted to study cortical bone thickness to predict the stability of mini-implants.…”
Section: Discussionmentioning
confidence: 99%
“…The principal determinants for mini-implant stability are mechanical retention, mini-implant design, quality and quantity of bone, and placement technique. 10 The firmness of cortical bone is one of the primary factors controlling the stability of mini-implants. 11 Several researchers have attempted to study cortical bone thickness to predict the stability of mini-implants.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Misch classification for implant placement, the MBS region has a dense cortical bone (D2), with an implant success rate of up to 90%, thus proving to be a popular treatment modality [ 7 ]. It is reported that the most significant factors in predicting MS stability include bone thickness, mechanical retention, screw design, and placement technique [ 8 ]. Motoyoshi et al reported that MS had a higher success rate when placed in an area with cortical bone thickness (CBT) ≥ 1 mm [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 The clinical success in the use of mini-implants is above 80% 2 ; however, failure cases are reported. 3 Many unsuccessful uses of mini-implants appear in the very early stages of placement and loading. Therefore, the primary stability is very crucial.…”
Section: Introductionmentioning
confidence: 99%
“…However, they have little effect on the created strains, and damage the bone by increasing the stresses around it. 3,8 The changes in the mini-implant design should be made with caution because the mechanical methods of controlling the stability are not accurate. 9,10 To solve this problem non-destructive mechanical methods such as FE analysis are used.…”
Section: Introductionmentioning
confidence: 99%